Botulinum Toxin A and physiotherapy in multiple sclerosis spasticity: Patient-tailored goal setting and the measurement of its achievement. Issue 1 (January 2019) - Butera, C.; Tronci, S.; Bianchi, F.; Guerriero, R.; Amadio, S.; Comola, M.; Esposito, F.; Radaelli, M.; Leocani, L.; Comi, G.; Del Carro, U.
Abstract : Botulinum toxin type A (BT-A) is known to be effective in improving focal spasticity; a few data are available on BT-A efficacy in improving function and quality of life in Multiple Sclerosis (MS). To evaluate in MS patients presenting with focal spasticity the grade of achievement of the predefined goals through the treatment with BT-A and physiotherapy a longitudinal prospective study was drawn in 11 patients; for each patient it was fixed an individualized rehabilitative program and BT-A was administered depending on spasticity pattern. The evaluation of the adequate achievement of the target was done at week 4 using the Goal Attainment Scale (GAS). Specific scales were applied depending on the function or disability domain involved. All of them had a progressive form of MS; EDSS was 6.5 mean (4–8). 8 patients had as target gait improvement, 2 postural changes and 1 posture improving. 9 out of 11 reached the fixed target, 6 of them with gait improvement as target. Our data suggest that an integrated, multidisciplinary approach in treating focal spasticity is effective for reaching the individualized objective targeted on actual needs of single patient. This is the first step for a subsequent evaluation of a real impact of our intervention in reducing global disability of MS patients.